14.EVALUATION OF THE ANTI-INFLAMMATORY EFFECT OF TELMISARTAN AS AN ADJUVANT THERAPY TO NSAID IN THE MANAGEMENT OF KNEE OSTEOARTHRITIS; A CLINICAL PROSPECTIVE STUDY (Iraqi Journal of Medical Sciences, 2018)
Background: Osteoarthritis (OA) is a degenerative joint disease caused by gradual loss of cartilage. Telmisartan is an angiotensin II receptor antagonist, and act as a partial agonist on the nuclear peroxisome proliferator-activated receptor-gamma (PPAR-?), that has been reported to exert anti-inflammatory effects.Objective: To evaluate the potential anti-inflammatory effect of telmisartan in patients with knee OA.Methods: Forty-two patients with painful knee OA were allocated into 2 groups, group (1): patients treated with naproxen tablets (500 mg/12 hr), telmisartan tablets (40 mg/day) and omeprazole (20 mg/day) for 3 months, while group (2): patients treated with naproxen tablets (500 mg/12 hr) and omeprazole (20 mg/day) for 3 months. The serum levels of IL-1?, high-sensitivity C-reactive protein (hs-CRP), TNF-? and erythrocyte sedimentation rate (ESR) were measured before and after 3 months of treatment.Results: Telmisartan when used in combination with naproxen resulted in significant decrease in serum levels of IL-1? and hs-CRP, higher than that produced by naproxen when used alone. The mean TNF-? level and ESR was decreased non-significantly in both study groups.Conclusion: Administration of telmisartan as an adjuvant therapy to naproxen in knee OA patients produced a significant decrease in the serum levels of IL-1? and hs-CRP, though no clear effect on TNF-? and ESR was noticed after 3 months treatment. Accordingly, many promising preventive strategies emerged from the available results since telmisartan relatively reduce the inflammatory burden in OA patients. The dose and duration of telmisartan treatment in this study did not indicate a risk of hypotension.Keywords: Telmisartan, naproxen, osteoarthritis, cytokinesCitation: Hmood SA, Mohammed MM, Kamal YM, Jasim NA. Evaluation of the anti-inflammatory effect of telmisartan as an adjuvant therapy to NSAID in the management of knee osteoarthritis; a clinical prospective study. Iraqi JMS. 2018; Vol. 16(1): 100-110. doi: 10.22578/IJMS.16.1.14
Keywords: Telmisartan; naproxen; osteoarthritis; cytokines